ALTERNATIF KEBIJAKAN PERSALINAN PADA IBU HAMIL MULTIGRAVIDA RIWAYAT SECTIO CAESAREA DI RUMAH SAKIT GRAHA JUANDA BEKASI - Manullang, Riyen Sari; Hardiana, Hedi (STIKes Medistra Indonesia, 2021)
The incidence of childbirth with actions in Indonesia increased. The results of the 2013 Riskesdas were delivered by sectio caesarean delivery by 9.8% with the highest proportion in DKI Jakarta (19.9%). This research is to find out alternative labor policies in multigravida pregnant women with a history of cesarean section. This type of research uses a qualitative method, in the implementation of this study is an interview guide during the interview, using the technique of triangulation of data sources and methods namely SWOT approach EFE, EFI, Matching Stage, Matrix SWOT and QSPM. The respondents in this study were 7 respondents from Graha Juanda Hospital Bekasi, by producing 4 alternative policies, namely the making of labor SOPs for multigravida pregnant women with history of SC making parenting keals, cooperating with Faske level I to conduct regular counseling, and adding facilities and infrastructure related to the hospital's tensile strength. The most dominant alternative to be carried out in accordance with the results of the analysis conducted, namely the making of SOPs for labor procedures for multigravida pregnant women with a history of elective and emergency SC needs to be separated and adjusted to their implementation